A design for EoL approach and metrics to favour closed-loop scenarios for products. Issue 3 (4th May 2017) - Favi, Claudio; Germani, Michele; Luzi, Andrea; Mandolini, Marco; Marconi, Marco
Abstract: Recently, environmentally conscious design and extended producer responsibility have become key aspects for companies that need to develop products that are sustainable along their whole life cycle. Design for End of Life (EoL) is a strategy that aims to reduce landfill waste through the implementation of closed-loop product life cycles. It is important to consider disassembly and EoL scenario management as early as the design phase. For these reasons, this paper presents an approach to help designers in the evaluation and subsequent improvement in product EoL performance. The method is based on four innovative EoL indices that compare different EoL scenarios for each product component. In this way, the designer can modify the product structure or the liaisons to maximise the reuse and remanufacture of components as well as material recycling. The presented case studies confirm the validity of the approach in helping designers during the redesign phase of goods and products to reduce the quantity of materials and industrial wastes sent to landfill.